ORANG BUGIS DALAM SILANG BUDAYA BAHARI DI PELABUHAN SUNDA KELAPA - Rifal Najering; M. Rasyid Ridha (Rayhan Intermedia, 2018)
This paper focuses on the Buginesse live in Sunda Kelapa Port. Generally, Port of Sunda Kelapa can be viewed as a connective center of voyage network broader people. By the encountering various cultures will enrich the horizon of Indonesian voyage world. This research will the culture translated in technological and social changes in seafarers' societies in Port of Sunda Kelapa. Before the presence of machine technology the sailors go trough of a long journey from Sunda Kelapa Port to other ports. For example, the trip from Palembang to Surabaya in the age of sail technology, it will take long time according to weather. But after the presence of machine technology, the journey is faster and the boats mobilization are more flexible, of course it has many positives impact to sailors income. The biggest challenge faced by the sail boats is the existence of the huge boats as big as tonnage with more loads, there is an unbalance competition between the traditional boats and the container boats. This research is a historical study by using qualitative method. Next the data will be processed in such manner by using historical method, like heuristic, critic, interpretation, and historiography.